Improvement of intratumor microdistribution of PEGylated liposome via tumor priming by metronomic S-1 dosing - Doi Y (Dove Medical Press, 2016)
Yusuke Doi,1 Amr S Abu Lila,1–3 Haruna Matsumoto,1 Tomoko Okada,1 Taro Shimizu,1 Tatsuhiro Ishida1 1Department of Pharmacokinetics and Biopharmaceutics, Institute of Biomedical Sciences, Tokushima University, Tokushima, Japan; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Zagazig University, Zagazig, Egypt; 3Department of Pharmaceutics, Faculty of Pharmacy, Hail University, Hail, Saudi Arabia Abstract: The efficient delivery of nanocarrier-based cancer therapeutics into tumor tissue is problematic. Structural abnormalities, tumor vasculature heterogeneity, and elevated intratumor pressure impose barriers against the preferential accumulation of nanocarrier-based cancer therapeutics within tumor tissues and, consequently, compromise their therapeutic efficacy. Recently, we have reported that metronomic S-1, orally available tegafur formulation, dosing synergistically augmented the therapeutic efficacy of oxaliplatin (l-OHP)-containing PEGylated liposome without increasing the toxicity in animal model. However, the exact mechanism behind such synergistic effect was not fully elucidated. In this study, therefore, we tried to shed the light on the contributions of metronomic S-1 dosing to the enhanced accumulation and/or spatial distribution of PEGylated liposome within tumor tissue. Tumor priming with metronomic S-1 treatment induced a potent apoptotic response against both angiogenic endothelial cells and tumor cells adjacent to tumor blood vessels, resulting in enhanced tumor blood flow via transient normalization of tumor vasculature, along with alleviation of intratumor pressure. Such a change in the tumor microenvironment imparted by S-1 treatment allows efficient delivery of PEGylated liposome to tumor tissue and permits their deep penetration/distribution into the tumor mass. Such a priming effect of S-1 dosing can be exploited as a promising strategy to enhance the therapeutic efficacy of nanocarrier-based cancer therapeutics suffering from inadequate/heterogeneous delivery to tumor tissues. Keywords: tumor microenvironment, metronomic chemotherapy, S-1, liposome, nanocarrier, EPR effect